Participatory food events as collaborative public engagement opportunities. Issue 2 (July 2019) - Pettinger, Clare; Parsons, Julie M; Letherby, Gayle; Cunningham, Miranda; Withers, Lyndsey; Whiteford, Andrew
There is an urgent need to 'get creative' with the way we tackle social and nutritional inequalities. The Food as a Lifestyle Motivator (FLM) project has explored the use of creative participatory approaches to engage 'harder to reach' communities in dialogues to improve their well-being and life skills. Preliminary findings have confirmed that food can be a powerful catalyst for social inclusion with the potential to empower 'marginalised' individuals. Part of this exploratory study has involved two participatory food events (November 2015 and November 2016) run in a local day centre for drug and alcohol rehabilitation. The aim of these events was to bring together key stakeholders (from the service user and provider communities) to exchange food-based knowledge, using collaborative and co-creative participatory approaches. Following ethical clearance, a range of data were collected at the events to assess their 'social impact'. These consisted of (1) audio interviews (service providers and users), (2) oral surveys (service users and key workers) and (3) observations of social cooking and eating engagement, and creative visual arts (photography, collage, food games and quizzes). In this article, we detail how the range of creative approaches used has successfully engaged individuals (average attendance: n = 80, service users: n = 32) to participate in these food-themed events. We reflect on the overarching themes from data capture of the social and therapeutic aspects of food (activities). We also reflect on the collation (and curation) of findings, systematically critiquing the approaches used, including consideration of ethics, and drivers for engagement. Finally, we consider how the utility of such creative approaches can optimise public engagement activities, not only to enhance research impact but also to inform collaborative developments with and between service users, service providers and other stakeholders, with the potential to lead to transformative food-related changes.